Risks of maladaptation: climate insurance in agriculture - Birgit Müller; Leigh Johnson; David Kreuer (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Weather risk is an issue of extraordinary concern in the face of climate change, not least for rural agricultural households in developing countries. Governments and international donors currently promote `climate insurance', financial mechanisms that make payouts following extreme weather events. Technologically innovative insurance programmes are heralded as promising strategies for decreasing poverty and improving resilience in countries that are heavily dependent on smallholder agriculture. New subsidies will amount to hundreds of millions of dollars, yet funders and advocates have thus far neglected the social and ecological ramifications of these policies. Reviews have focused largely on near-term economic effects and practical challenges. This briefing draws on an initial inventory of potential adverse effects of insurance programmes on local agricultural systems that we have recently assembled. Our review shows that farmers with insurance may alter their land-use strategies or their involvement in social networks previously used to mitigate climate risk. Both processes constitute crucial feedbacks on the environmental and the social systems respectively. Based on our study, we suggest preliminary principles for avoiding maladaptive outcomes, including recommendations for designing appropriate impact studies and insurance programmes. Before implementation, pilot projects should assess existing local risk-management strategies, financial instruments, and extant state agricultural and social protection policies. Participatory processes should be designed to anticipate and appraise potential effects of insurance – including those resulting from changing land use – and interactions with existing public policies. Several recommendations for improvements to the elaboration and design of future agricultural insurance programmes follow from our analysis: 1. Evaluate priorities 2. Encourage diversity 3. Adapt policies 4. Choose the right scale 5. Limit coverage to extremes 6. Tie insurance to ecologically sound strategies Current and future `climate insurance' projects should be combined with consciously designed programmes to invest in and foster farmer-led learning on sustainable agricultural techniques. Policies linking insurance coverage and subsidies to diversified and ecologically sensitive cultivation may provide new frameworks for the design of insurance programmes in developing countries. This also requires rethinking the accepted wisdom on bundling insurance with inputs, which may make social-ecological systems and smallholders more fragile and vulnerable in the face of a changing climate.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Umwelt; Ökosysteme und Ressourcen